Design Procedure of A Permanent Magnet D.C. Commutator Motor - Ritunjoy Bhuyan (GoAcademica Research & Publishing, 2021)
Electrical machine with electro magnet as excitation system many problems out of which, less efficiency is a major one. Self excited dc machine has to sacrifice some power for excitation system as a result, power available for useful work become less. This problem can be solved to some extent whatever may be the amount , by using permanent magnet for the excitation system of dc machine and there by contributing towards the conservation of conventional energy sources which are alarmingly decrease day by day . Using of permanent magnet in the electrical machine helps in burning of less conventional fossil fuel and contributes indirectly in conservation of air-pollution free environment. With permanent magnet dc motor, the efficiency of the machine also rise up considerably. This paper is an effort to give a computer aided design procedure of permanent magnet dc motor.